Management and optimization of chronic renal insufficiency in the setting of kidney cancer A Systematic Review - Jessica K Cobb; Hiroko Miyagi; Jad Chahoud; Claude Bassil; Philippe E. Spiess (International Brazilian Journal of Urology)
ABSTRACT Purpose: There is a bidirectional relationship between chronic kidney disease and the incidence of renal cell carcinoma. Despite the frequency of patients with both chronic kidney disease and renal cell carcinoma, there are limited systematic reviews detailing the nuanced treatment. This review provides comprehensive insights for clinicians for managing chronic kidney disease, and renal cell carcinoma. Methods and Methods: We reviewed published literature that examined either chronic kidney disease and renal cell carcinoma or an indirect contributor of both. Results: We compare and contrast renal cell carcinoma treatment with partial and radical nephrectomies, ablative techniques, and radiation and their impact on glomerular filtration rate, recurrence rate, and contraindications. We discuss when and how to intervene with treatment with emphasis on the delicate balance between eradicating malignancy and preserving renal function. Specifically, we detail the appropriate use of renal biopsies in incidentally discovered tumors, active surveillance, and postoperative surveillance including imaging sensitivity and specificity. We offer insight into the limitations of current systemic therapy, including renal toxicity. Conclusions: Our investigation into the intricate relationship between chronic kidney disease and renal cell carcinoma has many multifaceted challenges for both patients and healthcare providers face. This comprehensive review serves as an extensive synopsis of the current literature and offers patients the best possible long-term renal-based outcomes.